Attention in individuals with aphasia: Performance on the Conners' Continuous Performance Test – 2nd edition. Issue 2 (7th February 2020) - Lee, Jaime B.; Kocherginsky, Masha; Cherney, Leora R.
ABSTRACT: Studies suggest that individuals with aphasia present with impairments in attention. However, most research has been conducted with small sample sizes using experimental protocols that lack established psychometric properties. We examined the attention performance of 114 individuals with chronic post-stroke aphasia using a standardised, norm-referenced assessment of attention, the Conners' Continuous Performance Test-II (CPT-II; Conners, C. K. (2000). Conners' Continuous Performance Test II . Toronto: Multi-Health Systems Inc). Participants completed the CPT-II and the Western Aphasia Battery-Revised (WAB-R; Kertesz, A. (2007). Western Aphasia Battery-Revised . San Antonio, TX: PsychCorp). As a group, variable performance on selected CPT-II measures was observed. Participants demonstrated impairments on omissions (48.2%) and hit reaction time (67.5%), with 11.4% demonstrating atypically slow performance and over half of the sample (56.1%) performing atypically fast. The Confidence Index, a summary score, was also within the impaired range for the majority of participants. However, there were also measures in which a greater percentage of participants demonstrated performance within normal limits. Using the WAB-R Aphasia Quotient (AQ) as a measure of severity, there was significantly worse performance in participants with more severe (AQ < 50) compared to less severe (AQ ≥ 50) aphasia. No significant differences in attention were identified between participants with fluent versus non-fluent aphasia. The CPT-II is a feasible measure for persons with aphasia, which may assist in identifying attention performance deficits that potentially affect language.